Determinação socioeconômica e análise de valoração em saúde para o câncer de boca - Freire, Aldelany Ramalho (2023)
The elucidation of the role of socioeconomic factors on the involvement of individuals by oral cancer can support the implementation of public policies for social protection. Health economics studies are useful to ensure the rational use of resources, given the social contexts of users, making implemented policies more effective. The objective was to investigate the influence of socioeconomic factors on oral cancer rates, in addition to performing a health valuation analysis about the disease. This is a quantitative, analytical study, with five analysis plans (AP). AP 1 evaluated the effect of socioeconomic factors on the frequency of diagnoses of oral mucosa alterations and the number of hospitalizations for oral and oropharyngeal cancer in Brazil. AP 2 assessed the influence of socioeconomic indicators and investments on oral cancer mortality rates in Latin America. AP 3 verified the effect of coverage of public oral health services and socioeconomic indicators on the frequency of hospitalizations and cancer mortality in Brazil. AP 4 assessed the impact of socio-demographic characteristics on the prevalence of oral cancer at an advanced clinical stage in Brazil. In these ecological studies, the data came from official information systems, with public access. Significant associations between independent variables and outcomes were calculated using multivariate logistic regression models, considering p<0,05 and 95%CI. AP 5 consisted of a field study of health utility analysis for oral cancer, verifying the influence of socioeconomic context e oral health status, through Standard Gamble (SG) and Willingness to Pay(WTP). Multivariate Poisson and Negative Binomial regressions were developed, considering p<0.05 and 95%CI. Results of AP 1 demonstrated a higher frequency of diagnoses of mucosal changes and hospitalization of patients with oral cancer in more developed cities (B=11,298; p<0,001) and with greater inequality (B=11,614; p<0,001) in Brazil, while cities with greater inequality (B=8,159; p<0,001), higher proportion of inadequate basic sanitation (B=0,09; p=0,001), lower expectation of years of schooling (B=-0,718; p <0,001) and higher illiteracy rates (B=0,191; p<0,001) had a higher frequency of hospitalized patients with oral and oropharyngeal cancer. In AP 2, male individuals, aged 60 years or older (PR=14,7), residing in countries with greater inequality (PR=1,05), higher per capita health spending (PR = 1,09) and higher investments in research and development (PR = 1,81), were associated with a higher mortality rate from oral cancer in Latin America. The AP 3 verified that Brazilian cities with larger population and Human Development Index, more unequal and with lower coverage of oral health services had a higher risk of occurrence of cases and frequency of deaths from oral cancer. Regarding AP 4, a higher prevalence of oral cancer in advanced clinical stage in Brazil was observed in individuals with higher education, no partner and older (p<0,001). For health utility analysis of oral cancer (AP 5) younger participants (B=-0,250; p=0,023) and those with less schooling (B=-0,767; p<0,001) showed lower SG for a possible treatment. For WTP, male individuals (B=-1,821; p<0,001) with lower income (B=- 1,396; p=0,016) and greater impact of oral health on quality of life (B=-0,066; p<0,001) would be willing to pay less for a treatment. It is concluded that socioeconomic factors are strongly associated with diagnoses, hospitalizations and deaths due to oral cancer, with inequality, low education, offer of oral health services, gender and age being relevant factors. In addition, the socioeconomic context influences in preferences and decisions of individuals regarding health care and treatments for oral cancer.